Western Frontier of Orion, Gove County, Kansas - Zerr, Brad (Kansas State University. Dept. of History, 2011)
This study of the slowly-vanishing town of Orion explores the western Kansas environment and the founding of a community in 1886. Wheat farmers claimed large farms in this area. Named for a schoolteacher, Orion had a vital life through World War II, when a gunnery range kept it vitalized. A few buildings, an abandoned store, and a cemetery remain. This study contains on-site photographs and personal research by the author.
Keywords: Gove County; Orion; Aerial gunnery range; Gaeland Cemetery; Orion Methodist Church